2020
DOI: 10.1002/tpg2.20050
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping of resistance to emerging stem rust pathogen races in spring wheat using genotyping‐by‐sequencing

Abstract: The identification and characterization of resistance genes should outpace the rapid emergence of new P. graminis f. sp. tritici races, such as TTRTF and TTKTT, to mitigate stem rust damage to wheat. The objective of the current study was to identify and characterize P. graminis f. sp. tritici race resistance association signals. A total of 250 North American spring wheat lines were evaluated at the seedling stage with a total of seven isolates including TKKTP, TKTTF, TKTTF, TRTTF, TTRTF, TTKSK, and TTKTT. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 54 publications
(86 reference statements)
3
14
1
Order By: Relevance
“…A QTL at the 651-Mb region associated with seedling resistance against race TTKSK maps a region close to a QTL flanking marker (wPt5857, 1 Mb away) reported by Yu et al (2012) and a region associated with barc78 (4 Mb away) reported by Letta et al (2014) (Figure 3; Supplemental Table S1). A region at 718 Mb (718944322 bp) associated with seedling resistance to race TKTTF collocates with several markers reported by Bajgain et al (2015b) including IWB34733, IWB3569, and IWB61312 (809 kb away) for seedling resistance of spring wheat collections against TKTTF, marker IAAV3545 (809 kb) reported by Edae et al (2018) for seedling resistance of spring wheat against race RCRSC, several markers reported by Edae and Rouse (2020) for resistance of spring wheat against races TKTTF isolate from Ethiopia, (TKKTF-ETH, the closest marker is 5.6 Mb away) and TTRTF (2 Mb away), marker IWA4651 (324 kb) linked to Sr7a reported by Gao et al (2017) for seedling resistance of spring wheat against race TTTTF (Figure 4; Supplemental Table S2). Olivera et al (2015) and Bajgain et al (2015b) reported that Sr7a is effective against race TKTTF isolate from Ethiopia but not against the isolate from Germany (Olivera Firpo et al, 2017).…”
Section: 13mentioning
confidence: 54%
See 4 more Smart Citations
“…A QTL at the 651-Mb region associated with seedling resistance against race TTKSK maps a region close to a QTL flanking marker (wPt5857, 1 Mb away) reported by Yu et al (2012) and a region associated with barc78 (4 Mb away) reported by Letta et al (2014) (Figure 3; Supplemental Table S1). A region at 718 Mb (718944322 bp) associated with seedling resistance to race TKTTF collocates with several markers reported by Bajgain et al (2015b) including IWB34733, IWB3569, and IWB61312 (809 kb away) for seedling resistance of spring wheat collections against TKTTF, marker IAAV3545 (809 kb) reported by Edae et al (2018) for seedling resistance of spring wheat against race RCRSC, several markers reported by Edae and Rouse (2020) for resistance of spring wheat against races TKTTF isolate from Ethiopia, (TKKTF-ETH, the closest marker is 5.6 Mb away) and TTRTF (2 Mb away), marker IWA4651 (324 kb) linked to Sr7a reported by Gao et al (2017) for seedling resistance of spring wheat against race TTTTF (Figure 4; Supplemental Table S2). Olivera et al (2015) and Bajgain et al (2015b) reported that Sr7a is effective against race TKTTF isolate from Ethiopia but not against the isolate from Germany (Olivera Firpo et al, 2017).…”
Section: 13mentioning
confidence: 54%
“…Chromosome 6A harbored six QTL represented by single and multiple markers Figures 3,4,7,and 9). A QTL at 5 Mb (5,058,172 bp) region associated with field resistance in TKTTF_MS18 is very close to QTL tagging markers IWA7913 (138 kb) and IWB23519 (146 kb) reported by Bajgain et al (2015b), IWB72958 (138 kb) reported by Nirmala et al (2017) as a predictive marker for Sr8155B1, markers IWA7913 (138 kb), and S6A_PART1_3015737/S6A_PART1_3206675 (2 Mb away) The Plant Genome associated with Sr8a reported by Guerrero-Chavez et al (2015) and Edae and Rouse (2020), respectively. Sr8155B1 is effective against several races but not TTKSK and JRCQC at the seedling stage (Nirmala et al, 2017) and Sr8a is ineffective against race TKTTF (Olivera et al, 2015).…”
Section: 13mentioning
confidence: 66%
See 3 more Smart Citations